Effects of soil solarization on purple nutsedge population density and on productivity of vegetable crops under organic cultivation - Ricci, Marta dos Santos Freire; Almeida, Dejair Lopes de; Fernandes, Maria do Carmo Araújo; Ribeiro, Raul de Lucena Duarte; Cantanheide, Maria Cláudia dos Santos (Pesquisa Agropecuaria Brasileira, 2000)
A field experiment was carried out at Seropédica, state of Rio de Janeiro, Brazil, to evaluate the effects of soil solarization on purple nutsedge (Cyperus rotundus) weed population and on productivity of vegetable crops under organic cultivation. Solarization was accomplished by covering the soil surface with transparent polyethylene sheets (50 mm) for a period of 210 days. The mean temperature at 0-10 cm soil layer was about 23% higher than that of unsolarized plots. Following plastic removal the area was planted with carrot (Daucus carota 'Brasília'), cabbage (Brassica oleracea var. capitata 'Astrus'), garden beet (Beta vulgaris 'Tall Top Early Wonder'), and dwarf greenbean (Phaseolus vulgaris 'Alessa'). In general, soil solarization reduced purple nutsedge population by 59%. There was a significant increase in yields of carrot (28%), cabbage (34%), beet (37%), and greenbean (32%) when compared to unsolarized plots. Biological nitrogen fixation, as judged by greenbean nodulation, was not affected by solarization but the soil nematode population was considerably reduced.